‘No Person Shall Sell Goods at an Unjust Profit’: A Review of Consumer Price Controls in Southern Rhodesia, 1939-1949 (Historia, 2022)
This article explores the regime of consumer price controls instituted in Southern Rhodesia during World War II and continued in the post-war period up to 1949. The ‘war effort’ required the colony to change rapidly and tackle emerging shortages, bottlenecks, and general wartime disruptions. Southern Rhodesia responded to rising consumer prices and the spiralling cost of living by assembling price control officials, institutions, legislation and policies. Besides evaluating the immediate outcome of consumer price controls, the article also examines their socioeconomic impact. It argues that while the first few years saw some success in stabilising prices and curtailing price hikes, controls incentivised contravention and other unscrupulous practices as businesses sought to realise profits. Furthermore, controls sacrificed industrial competitiveness because businesses had little incentive to improve their production methods. On consumer price controls extended to Africans in this colonial society, the article argues that the measures were socially retrogressive because they slowed down the emergence of African business enterprises in rural areas while also stifling African wages in urban areas. Thus, while deliberately protecting white consumers, consumer price controls simultaneously enforced African under-consumption to maintain the settler colonial model.
Keywords: Consumer price controls; consumers; contravention; Southern Rhodesia; shortages; war effort; Africans